2021
DOI: 10.1038/s41467-021-25282-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T cells are able to efficiently eliminate cancer cells by additive cytotoxicity

Abstract: Lethal hit delivery by cytotoxic T lymphocytes (CTL) towards B lymphoma cells occurs as a binary, “yes/no” process. In non-hematologic solid tumors, however, CTL often fail to kill target cells during 1:1 conjugation. Here we describe a mechanism of “additive cytotoxicity” by which time-dependent integration of sublethal damage events, delivered by multiple CTL transiting between individual tumor cells, mediates effective elimination. Reversible sublethal damage includes perforin-dependent membrane pore format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 67 publications
0
132
0
Order By: Relevance
“…This is possible when the biological process of interest can be monitored with lower frame rates or image resolution. For example, studying cancer cell invasion only requires image acquisition with 10 min intervals, which allows effective heat dissipation during image acquisition; conversely, high scan rates required for calcium imaging deeply inside the tumor (20 s) may require a higher repetition rate of excitation pulses and preclude effective deep imaging in highly scattering tissue ( Weigelin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possible when the biological process of interest can be monitored with lower frame rates or image resolution. For example, studying cancer cell invasion only requires image acquisition with 10 min intervals, which allows effective heat dissipation during image acquisition; conversely, high scan rates required for calcium imaging deeply inside the tumor (20 s) may require a higher repetition rate of excitation pulses and preclude effective deep imaging in highly scattering tissue ( Weigelin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tumors are dense, opaque, three-dimensional objects with a size of millimeters to centimeters, which causes strong light scattering ( Andresen et al, 2009 ). In addition, analysis of the tumor microenvironment requires to detect multiple cell types, their morphology and activation states simultaneously, and tissue structures over time through a body window ( Weigelin et al, 2021 ). HighIR combined with 3P microscopy enables the label-free detection of metabolites, tissue morphology, and leukocyte migration in mammary tumor microenvironment in vivo ( You et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…There are two major subtypes of T cells: CD8+ and CD4+ T cells [ 16 ]. CD8+ T cells, also known as killer T cells, directly kill virus-infected cells and cancer cells [ 17 ]. In contrast, CD4+ T cells play an indirect role in the death of infected cells by determining whether and how the immune system responds to a perceived threat or by regulating other immune cells through cytokines [ 18 ].…”
Section: Immune Cells Targeting Nanoparticlesmentioning
confidence: 99%
“…While this ratio is lower than the previously mentioned <1:90 for CD19 agents, it is notable that bispecific T-cell engagers may benefit from lower E:T ratios in solid tumors due to the process of additive toxicity, as described by Weigelin et al in murine models of melanoma. 103 Cytolysis of solid tumor cells may be induced by sequential 'sublethal' interactions between CTLs and tumor cells (such as granzyme B-mediated damage to the nuclear envelope and the creation of double-stranded breaks in DNA). 103 104 Bispecific T-cell engagers may help to promote this effect on solid tumors by acting as a stabilizing contact which can increase these sublethal CTL interactions at the tumor site.…”
Section: Development and Challenges Facing T-cell Engagers In Intracranial Malignancymentioning
confidence: 99%
“…103 104 Bispecific T-cell engagers may help to promote this effect on solid tumors by acting as a stabilizing contact which can increase these sublethal CTL interactions at the tumor site. 35 103 Choi et al also reported that bispecific T-cell engager therapy could redirect T regs in vitro to express granzymes and perforins, which may serve to induce further tumor cytolysis. 34 Accordingly, the use of bispecific T-cell engagers in murine models of intracranial glioma has been shown to achieve durable and complete cures in up to 75% of mice (p<0.05).…”
Section: Development and Challenges Facing T-cell Engagers In Intracranial Malignancymentioning
confidence: 99%